2016
DOI: 10.1007/s00429-016-1221-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of growth hormone-responsive cells in the mouse brain

Abstract: Growth hormone (GH) exerts important biological effects primarily related to growth and metabolism. However, the role of GH signaling in the brain is still elusive. To better understand GH functions in the brain, we mapped the distribution of GH-responsive cells and identified the receptors involved in GH central effects. For this purpose, mice received an acute intraperitoneal challenge with specific ligands of the GH receptor (mouse GH), prolactin receptor (prolactin) or both receptors (human GH), and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 57 publications
7
82
2
6
Order By: Relevance
“…This suggests that central GH signaling might be involved in energy expenditure and glucose homeostasis through a central mechanism [10]. GH overexpression in the CNS results in hyperphagia-induced obesity, insulin resistance, and increased circulating GH levels [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that central GH signaling might be involved in energy expenditure and glucose homeostasis through a central mechanism [10]. GH overexpression in the CNS results in hyperphagia-induced obesity, insulin resistance, and increased circulating GH levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also indicate that leptin can modulate GH secretion and the GH response to GHRH [22]. LepRb neurons are widely distributed within the hypothalamic ARH, VMH, DMH, LHA, and some additional sites that also express GHR [10], [23]. Recent transcriptome analysis of LepRb expressing neurons revealed that the Ghr gene is strongly enriched in LepRb neurons [24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, pSTAT5 immunoreactivity observed in this group reveals signalling exclusively through the PRLR-l. Still, GH (Furigo et al 2016) or leptin could contribute to the pSTAT5-ir observed in pregnant females, although the high levels of PLs likely account for most (if not all) of the pSTAT5 immunolabelling observed. Regarding leptin, STAT3 is the main STAT member associated with the leptin receptor (Ladyman et al 2012), whereas STAT5 phosphorylation associated with leptin signalling has been reported only in the arcuate nucleus (Gong et al 2007;Mütze et al 2007) and has not been replicated in all studies (Vaisse et al 1996).…”
Section: Immunohistochemical Detection Of Pstat5 As a Measure Of Centmentioning
confidence: 94%
“…Regarding leptin, STAT3 is the main STAT member associated with the leptin receptor (Ladyman et al 2012), whereas STAT5 phosphorylation associated with leptin signalling has been reported only in the arcuate nucleus (Gong et al 2007;Mütze et al 2007) and has not been replicated in all studies (Vaisse et al 1996). As for GH, regions of the brain showing high levels of expression of GH receptors and responsiveness to GH (detected by pSTAT5-ir; Furigo et al 2016), such as the hippocampus and dentate gyrus (Burton et al 1992) or layers 2, 3, and 5, and especially, layer 6 of the cerebral cortex (Lobie et al 1993), show no pSTAT5 labelling in any of our mice, neither in virgin nor in pregnant or lactating females. This suggests that GH signalling in the brain is taking place through alternative pathways, e.g., those involving Src kinases (Waters 2015).…”
Section: Immunohistochemical Detection Of Pstat5 As a Measure Of Centmentioning
confidence: 99%